Partial Lyα thermalization in an analytic nonlinear diffusion model - Wolschin, Georg (Scientific reports, 2024)
During recombination, the cosmic background radiation is disturbed, in particular, by Lyman-alpha emissions from neutral hydrogen. It is proposed to account for the subsequent time-dependent partial thermalization of the Ly$$α$$energy content in an analytically solvable nonlinear diffusion model. The amplitude of the partially thermalized and redshifted Ly$$α$$line is found to be too low to be visible in the cosmic microwave spectrum, in accordance with previous numerical models and Planck observations.
Gesehen am 09.08.2024